On the Pile Response to Inclined Loads. (2016) - Conte, Enrico; Troncone, Antonello; Vena, Mirko
Abstract: In this paper, a three-dimensional finite element approach is used to analyse the response of reinforced concrete piles to inclined loads. Appropriate constitutive models are considered to account for the nonlinear behaviour of the pile and the soil. In particular, the occurrence of plastic strains in the soil, concrete cracking and steel yielding in the pile are reliably simulated. Some characteristic aspects of the behaviour of piles under inclined loads are highlighted.